2017
DOI: 10.1001/jamaneurol.2017.1397
|View full text |Cite
|
Sign up to set email alerts
|

Large Perivascular Spaces Visible on Magnetic Resonance Imaging, Cerebral Small Vessel Disease Progression, and Risk of Dementia

Abstract: IMPORTANCE With advancing age, an increased visibility of perivascular spaces (PVSs) on magnetic resonance imaging (MRI) is hypothesized to represent impaired drainage of interstitial fluid from the brain and may reflect underlying cerebral small vessel disease (SVD). However, whether large perivascular spaces (L-PVSs) (>3 mm in diameter) visible on MRI are associated with SVD and cognitive deterioration in older individuals is unknown.OBJECTIVE To examine whether L-PVSs are associated with the progression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
131
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(150 citation statements)
references
References 39 publications
6
131
0
4
Order By: Relevance
“…58,76,77,83,88,90,91,[97][98][99] Of note, for 7 studies, association results of CMB with recurrent stroke or ICH risk were obtained from 3 previously published meta-analyses. 78,100,101 Regarding PVS, 5 studies were included: 3 for stroke, 18,102,103 2 for dementia, 104,105 and 2 for death. 102,103 White Matter Hyperintensity Burden…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…58,76,77,83,88,90,91,[97][98][99] Of note, for 7 studies, association results of CMB with recurrent stroke or ICH risk were obtained from 3 previously published meta-analyses. 78,100,101 Regarding PVS, 5 studies were included: 3 for stroke, 18,102,103 2 for dementia, 104,105 and 2 for death. 102,103 White Matter Hyperintensity Burden…”
Section: Resultsmentioning
confidence: 99%
“…As well as integrating information on multiple MRI markers of VBI, our review adds numerous new studies. 14,16,[18][19][20][21][24][25][26]28,29,32,33,35,36,41,46,[49][50][51]57,58,64,72,75,84,88,95,96,99,[102][103][104][105] We also present, to our knowledge, the first metaanalyses on the association of BI with stroke subtypes, dementia, and mortality and the first systematic review on the association of PVS with stroke, dementia, and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen articles met the aforementioned criteria ( Fig. 1) [16][17][18][19][20][21][22][23][24][25][26][27][28]. Three studies analyzed longitudinal data [16,17,19] and ten were cross-sectional studies [18,[20][21][22][23][24][25][26][27][28].…”
Section: Resultsmentioning
confidence: 99%
“…Many studies determined a strong correlation between increased perivascular clearance and cognitive impairment. Based on clinical study results, Ding et al [59] reported that 3-mm EPVS was associated with cognitive decline and vascular dementia. Maclullich et al [60] showed that EPVS may lead to nerve fiber destruction in the basal ganglia associated with cognitive functions, resulting in the reduction of nonverbal reasoning and visuospatial ability.…”
Section: Enlarged Perivascular Spacesmentioning
confidence: 99%